2023
DOI: 10.3390/jfmk9010011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coastal Walking Outdoors and Virtual Reality Indoor Walking on Heart Rate, Enjoyment Levels and Mindfulness Experiences in Healthy Adults

Gianpiero Greco,
Claudio Centrone,
Luca Poli
et al.

Abstract: Outdoor exercise is beneficial for psychophysical well-being. Limited studies have compared outdoor and virtual reality (VR) indoor physical activities, especially in coastal settings. Therefore, this study aimed to assess the impact of outdoor coastal walking and indoor walking in a VR simulation with a similar environment on physiological and psychological variables in healthy adults. A total of 26 subjects (14 M and 12 F, age 25.2 ± 2.5 years) voluntarily participated in this crossover randomized controlled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Main activity (Exergame): through the immersive virtual reality of this system (Homing ® , Tecnobody, Bergamo, Italy), it was possible to replicate movements in virtual environments and provide visual and auditory feedback necessary to correct performance. This 6 min phase involved using one of the interactive activities available that simulated a low-/moderate-intensity walk at a predetermined speed of 4.5 km/h [ 67 , 68 ]. Cooldown: consisted of relaxation exercises and static stretching (2 min duration).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main activity (Exergame): through the immersive virtual reality of this system (Homing ® , Tecnobody, Bergamo, Italy), it was possible to replicate movements in virtual environments and provide visual and auditory feedback necessary to correct performance. This 6 min phase involved using one of the interactive activities available that simulated a low-/moderate-intensity walk at a predetermined speed of 4.5 km/h [ 67 , 68 ]. Cooldown: consisted of relaxation exercises and static stretching (2 min duration).…”
Section: Methodsmentioning
confidence: 99%
“…Following 4 h of work, each participant performed the three weekly assigned conditions for ten minutes in a random and counterbalanced order: Each Outdoor Physical Active Break (OPAB) session lasted 10 min, divided into 3 phases: Warm-up: aimed to increase heart rate, improve muscular blood flow, and prepare major joints for the subsequent work phase (2 min duration). Main activity (Outdoor Walk): consisted of a low-/moderate-intensity walk in the outdoor work environment (6 min duration, predetermined speed of 4.5 km/h) [67,68]. Cooldown: consisted of relaxation exercises and static stretching (2 min duration).…”
Section: Physical Activity Break Interventionsmentioning
confidence: 99%
“…In detail, outdoor exercise (also named green exercise) concerns the practice of physical activity or exercise in natural environments; it is characterized by easy accessibility and mainly uses walking as a type of exercise [18]. The benefits of nature exposure on psychophysiological health are documented in the literature, and this exercise setting can also counteract conditions caused by urban living such as air pollution, urban noise, and crowding [27,28]. For example, a recent systematic review has shown that Nordic Walking can represent a safe and accessible outdoor exercise for the elderly population, improving cardiovascular function, balance ability, and quality of life.…”
Section: Introductionmentioning
confidence: 99%